2004
DOI: 10.1109/tmi.2004.824237
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Shape Modeling Using Deformable Superellipses for Prostate Segmentation

Abstract: Automatic prostate segmentation in ultrasound images is a challenging task due to speckle noise, missing boundary segments, and complex prostate anatomy. One popular approach has been the use of deformable models. For such techniques, prior knowledge of the prostate shape plays an important role in automating model initialization and constraining model evolution. In this paper, we have modeled the prostate shape using deformable superellipses. This model was fitted to 594 manual prostate contours outlined by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
121
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 45 publications
4
121
0
1
Order By: Relevance
“…Deformable models have been widely used for medical image segmentation [5,6,7,8,9] and are generally more successful than the former methods. Fitting ellipses, ellipsoids, super-ellipses, and deformable ellipses or using them for initialization have been relatively attractive approaches for prostate segmentation due to the shape of the gland [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformable models have been widely used for medical image segmentation [5,6,7,8,9] and are generally more successful than the former methods. Fitting ellipses, ellipsoids, super-ellipses, and deformable ellipses or using them for initialization have been relatively attractive approaches for prostate segmentation due to the shape of the gland [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While the extensive study of [12] showed good segmentation results, the method presented is limited to 2D. Previous 3D methods [15,16] are time consuming (> 2 minutes) or require significant user intervention [11].…”
Section: Introductionmentioning
confidence: 99%
“…The model selectively discarded salient points for building the shape model to improve segmentation accuracy in presence of shadow artifacts in TRUS images. Gong et al 8 proposed to use deformable super ellipse to segment the prostate. Shape constraints of the model was effective in achieving impressive segmentation results.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little literature on automated segmentation of treated sites during RF ablation, segmentation techniques for US images have been reported for applications with echocardiographic (e.g., Corsi et al 2002;Angelini et al 2005), breast (e.g., Horsch et al 2002;Chang et al 2003a) and prostate data (e.g., Shen et al 2003;Gong et al 2004). Because of characteristic US artefacts, such as speckle and shadowing, intensity inhomogeneities, low contrast and ill-defined boundaries, simple image feature-based thresholding or edge-detection methods are ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Because of characteristic US artefacts, such as speckle and shadowing, intensity inhomogeneities, low contrast and ill-defined boundaries, simple image feature-based thresholding or edge-detection methods are ineffective. Successful segmentation algorithms reported for US images are based on morphologic operations (Czerwinski et al 1999;Gong et al 2004), neural networks (Binder et al 1999), wavelet analysis (Angelini et al 2001) and Markov random fields (Haas et al 2000;Xiao et al 2002;Brusseau et al 2004;Gong et al 2004). These incorporate preprocessing for speckle reduction (e.g., the "stick" method) (Czerwinski et al 1999), anisotropic diffusion (Perona and Malik 1990) and intensity corrections (Xiao et al 2002).…”
Section: Introductionmentioning
confidence: 99%